2019
DOI: 10.1038/s41598-019-38738-w
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized controlled trial on the influence of dietary intervention on epigenetic mechanisms in children with cow’s milk allergy: the EPICMA study

Abstract: Epigenetic mechanisms could drive the disease course of cow’s milk allergy (CMA) and formula choice could modulate these pathways. We compared the effect of two different dietary approaches on epigenetic mechanisms in CMA children. Randomized controlled trial on IgE-mediated CMA children receiving a 12-month treatment with extensively hydrolyzed casein formula containing the probiotic L.rhamnosus GG (EHCF + LGG) or with soy formula (SF). At the baseline, after 6 and 12 months of treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 42 publications
1
68
0
1
Order By: Relevance
“…This study demonstrated that treatment with EHCF+LGG is characterized by a more pronounced effect on FoxP3 demethylation compared to soy formula and by a higher methylation status of IL-4 and IL-5 and a lower methylation status of IL-10 and IFN-γ (17). Moreover, children treated with EHCF+LGG showed a selected miRNA expression toward a Th1-oriented response, leading to the activation of immune tolerance mechanisms (17). However, the impact of diet on epigenetic mechanisms may not only be direct but also mediated by the GM (84).…”
Section: Potential Mechanisms Of Action Of Infant Formulasmentioning
confidence: 67%
See 3 more Smart Citations
“…This study demonstrated that treatment with EHCF+LGG is characterized by a more pronounced effect on FoxP3 demethylation compared to soy formula and by a higher methylation status of IL-4 and IL-5 and a lower methylation status of IL-10 and IFN-γ (17). Moreover, children treated with EHCF+LGG showed a selected miRNA expression toward a Th1-oriented response, leading to the activation of immune tolerance mechanisms (17). However, the impact of diet on epigenetic mechanisms may not only be direct but also mediated by the GM (84).…”
Section: Potential Mechanisms Of Action Of Infant Formulasmentioning
confidence: 67%
“…Moreover, the production of the tolerogenic cytokine IL-10 was higher in Jurkat T cells that underwent a casein hydrolysate stimulus (79). Preliminary data by our group suggest that formula choice is able to induce immune system modulation through epigenetic mechanisms in CMA infants (17,82,83); specifically, evidence suggests that EHCF+LGG is able to modulate GM, raising the abundance of selected genera (Roseburia, Coprococcus, and Blautia) with increased production of butyrate (16). A significant difference in DNA methylation of Th2 and Th1 cytokine (IL-4, IL-5, IL-10, and IFN-γ) genes and of FoxP3, the transcription factor that modulates the fate of Tregs, was observed in infants treated with EHCF+LGG who develop immune tolerance compared to children who received other formulas (82,83).…”
Section: Potential Mechanisms Of Action Of Infant Formulasmentioning
confidence: 80%
See 2 more Smart Citations
“…One of the most promising types of therapy is based on nutrigenomics. The role of foetal programming in the prevention and therapy of various inflammatory and atopic diseases are also the widely discussed randomized controlled trials on the influence of dietary intervention on epigenetic mechanisms in children who suffered from cow’s milk allergy that have already done [ 12 ] Maternal dietary patterns may prevent or reduce hypersensitivity with significant reduction especially in IgG-mediated diseases [ 13 ]. A successful protocol for IgE-mediated reactions still remains a challenge, but there have been several studies published describing correlations between maternal dietary components that works preventively through epigenetic activation of mechanisms against asthma, wheezing and allergic rhinitis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%